Village of the vampire cat - Namioka, Lensey (Boston : Tuttle Pub., 2005)
When a young ronin returns to the village of his former teacher, he and his companion find it being terrorized by a mysterious killer
Teenager ages 13-18 years old (blue)
Keywords: Samurai -- Fiction; Japan -- Fiction